Melatonin prevents experimental central serous chorioretinopathy in rats. Issue 1 (29th April 2022) - Yu, Shanshan; Cui, Kaixuan; Wu, Peiqi; Wu, Benjuan; Lu, Xi; Huang, Rong; Tang, Xiaoyu; Lin, Jianqiang; Yang, Boyu; Zhao, Jinfeng; He, Qingjing; Liang, Xiaoling; et al.
Abstract: Central serous chorioretinopathy (CSC) is a vision‐threatening disease with no validated treatment and unclear pathogenesis. It is characterized by dilation and leakage of choroidal vasculature, resulting in the accumulation of subretinal fluid, and serous detachment of the neurosensory retina. Numerous studies have demonstrated that melatonin had multiple protective effects against endothelial dysfunction, vascular inflammation, and blood–retinal barrier (BRB) breakdown. However, the effect of melatonin on CSC, and its exact pathogenesis, is not well understood thus far. In this study, an experimental model was established by intravitreal injection of aldosterone in rats, which mimicked the features of CSC. Our results found that melatonin administration in advance significantly inhibited aldosterone‐induced choroidal thickening and vasodilation by reducing the expression of calcium‐activated potassium channel KCa2.3, and attenuated tortuosity of choroid vessels. Moreover, melatonin protected the BRB integrity and prevented the decrease in tight junction protein (ZO‐1, occludin, and claudin‐1) levels in the rat model induced by aldosterone. Additionally, the data also showed that intraperitoneal injection of melatonin in advance inhibited aldosterone‐induced macrophage/microglia infiltration, and remarkably diminished the levels of inflammatory cytokines (interleukin‐6 [IL‐6], IL‐1β, and cyclooxygenase‐2), chemokines (chemokine C–C motif ligand 3, and C–X–C motif ligand 1), and matrix metalloproteinases (MMP‐2 and MMP‐9). Luzindole, as the nonselective MT1 and MT2 antagonist, and 4‐phenyl‐2‐propionamidotetraline, as the selective MT2 antagonist, neutralized the melatonin‐induced inhibition of choroidal thickening and choroidal vasodilation, indicating that melatonin might exert the effects via binding to its receptors. Furthermore, the IL‐17A/nuclear factor‐κB signaling pathway was activated by intravitreal administration of aldosterone, while it was suppressed in melatonin‐treated in advance rat eyes. This study indicates that melatonin could serve as a promising safe therapeutic strategy for CSC patients.